A comparison of magnetic, structural and thermal properties of NiFeCoMo high entropy alloy produced by sequential mechanical alloying versus the alloy produced by conventional mechanical alloying - Simsek, Tuncay; Akgul, Saban; Guler, Omer; Ozkul, Iskender; Avar, Baris; Chattopadhyay, Arun K.; Guler, Seval H. (Elsevier, 2021)
The soft ferromagnetic materials are of great industrial importance for their applications in magnetic cores for transformers, electric motors, inductors, and generators. In recent years, the trend has been to use magnetic high entropy alloys (HEAs) owing to their superior magnetic properties compared to the conventional magnetic materials. In this study, the traditional magnetic materials, (NiFeCo)(95)Mo-5 and (NiFeCo)(90)Mo-10 produced by conventional mechanical alloying method, were compared with the NiFeCoMo high entropy alloy produced by the sequential mechanical alloying method. Unlike conventional mechanical alloying, NiFeCoMo HEA was produced by mechanical alloying using sequential additions of Co and Mo to the preformed Fe-Ni alloy. Besides its magnetic properties, the effect of Co and Mo on the overall characteristics of the alloy was also investigated. In 60 h milled samples of the (NiFeCo)(95)Mo-5 and (NiFeCo)(90)Mo-10 alloys, the crystallite sizes were estimated as 10.5 and 10.8 nm respectively, whereas the crystallite size for the NiFeCoMo HEA was 15 nm. The presence of Mo in the alloy induced the formation of lamellar or layered structures of the particles. During the sequential milling to form NiFeCoMo HEA, it was noticed that the addition of Co into the preformed Fe-Ni alloy increased the magnetic saturation value due to the formation of FeCoNi alloy phase. However, further addition of Mo into the FeCoNi alloy phase reduced the magnetic saturation value of NiFeCoMo alloy significantly. After 60 h of milling the magnetic saturation value was dropped from 102.48 emu/g for the NiFeCo alloy to 60.52 emu/g for the NiFeCoMo alloy.
Keywords: Mechanical alloying; Magnetic materials; High entropy alloys; Sequential milling